2016
DOI: 10.1098/rspb.2016.1319
|View full text |Cite
|
Sign up to set email alerts
|

The heritability of chimpanzee and human brain asymmetry

Abstract: Human brains are markedly asymmetric in structure and lateralized in function, which suggests a relationship between these two properties. The brains of other closely related primates, such as chimpanzees, show similar patterns of asymmetry, but to a lesser degree, indicating an increase in anatomical and functional asymmetry during hominin evolution. We analysed the heritability of cerebral asymmetry in chimpanzees and humans using classic morphometrics, geometric morphometrics, and quantitative genetic techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 64 publications
(77 reference statements)
3
33
0
Order By: Relevance
“…If brain asymmetries reflect specific left or right hemisphere genetic regulation, then more lateralized brain regions would presumably have weaker interhemispheric correlations. This interpretation is supported by the results reported here, but whether this pattern could be expanded to additional brain regions remains unclear [58].…”
Section: (A) Genetic Factorssupporting
confidence: 85%
See 1 more Smart Citation
“…If brain asymmetries reflect specific left or right hemisphere genetic regulation, then more lateralized brain regions would presumably have weaker interhemispheric correlations. This interpretation is supported by the results reported here, but whether this pattern could be expanded to additional brain regions remains unclear [58].…”
Section: (A) Genetic Factorssupporting
confidence: 85%
“…However, very few individual genes have so far been implicated in any aspect of lateralization of the human brain [46][47][48][49], and the genetic determinants of cerebral asymmetries are unknown and remain elusive [19,50,51]. Studies in humans suggest that there is heritability of brain asymmetries, notably within the PT [52][53][54], but this issue has not been explored in a wide range of nonhuman primates [55][56][57][58] or, to any extent, in our closest living relatives, the chimpanzees.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, cortical asymmetry of the human brain may also be associated with interhemispheric differences in gene expression (78,79). Moreover, besides the directional asymmetry (DA) studied in this study, fluctuating asymmetry (FA), defined as the distance from the populationlevel mean directional asymmetry, reflects environmental influences during development but shows significant heritability (80). In future ENIGMA genome-wide association studies of brain asymmetries, both indexes may be included as the phenotypes.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, future research may also consider the degree of laterality (e.g., the unsigned magnitude of the asymmetry index) as being potentially both heritable and linked to other biological factors. Comparative analysis of human and chimpanzee data has indicated that the degree of laterality in either direction (left or right) may be a distinct and partly heritable aspect of human brain asymmetry (83).…”
Section: Discussionmentioning
confidence: 99%